The Influence of Employee Training and Employee Engagement Towards Employee Performance - Ade Sandra; Didin Hikmah Perkasa; Didip Diandra (Jurnal Manajemen dan Bisnis Madani, 2026)
This study examines the effects of employee training (X1) and employee engagement (X2) on employee performance (Y) at Taruna Bhakti vocational senior high school in Depok City. A quantitative research approach was employed, involving two independent variables and one dependent variable. Data were collected using a structured questionnaire distributed through the Google Forms platform to the 51 study respondents, representing the total number of employees. The data were analyzed using SPSS software (version 31) and SmartPLS, with responses measured on a five-point Likert scale. The empirical results confirm that employee training and employee engagement serve as significant positive predictors of employee performance. The findings indicate that training initiatives enhance teachers’ pedagogical, technical, and interpersonal competencies, while high levels of engagement strengthen vigor, dedication, and proactive involvement in professional roles.